BIO-EFFICACY OF CYANTRANILIPROLE 10% OD- AN ANTHRANILIC DIAMIDE INSECTICIDE AGAINST SUCKING PESTS OF COTTON - R. D. PATEL; T. M. BHARPODA; N. B. PATEL; P. K. BORAD (The Bioscan, 2014)
Field studies were conducted during two consecutive kharif seasons of 2010-11 and 2011-12 in order to evaluate the field bio-efficacy of a newer molecule cyantraniliprole 10% OD (Cyazypyr @ 45, 60, 75, 90 and 105 g a.i./ ha) along with indoxacarb 14.5 SC (Avaunt @ 75 g a.i./ha) and endosulfan 35 EC (Thiodan @ 350 g a.i./ha) as standard checks against the cotton aphid, Aphis gossypii Glover; thrips, Thrips tabaci Lindeman and whitefly, Bemisia tabaci (Gennadius). The two higher doses of cyantraniliprole 10% OD i.e. 90 and 105 g a.i./ha was found highly effective in managing the population of aphid, thrips and whitefly during both the year compared to endosulfan and indoxacarb. The seed cotton yield was recorded significantly higher in treatments cyantraniliprole 10% OD @ 90 (31.97 q/ha) and 105 (33.33 q/ha) g a.i./ha with an increase of 50.80 and 52.81 per cent over untreated control, respectively. Considering the bio-efficacy and yield, cyantraniliprole 10% OD @ 90 g a.i./ha is recommended for effective control of sucking pests in cotton ecosystem.